P073 Evaluation of DPPH free radical scavenging activity by HPLC technique: a screening method for drugs and nutrients used in inflammatory bowel disease. (25th January 2019) - Jelicic, M-L; Brusac, E; Amidzic Klaric, D; Nigovic, B; Turk, N; Krznaric, Z; Mornar, A
Abstract: Background: Oxidative stress is considered as one of the etiopathogenetic factors involved in development of inflammatory bowel disease (IBD). In this context, recent studies have suggested that the drugs and biologically active compounds with additional antioxidant activity may be beneficial in the treatment of IBD. Scavenging of α, α-diphenyl-β-picrylhydrazyl (DPPH) free radical is the basis of a common antioxidant assay. Therefore, the focus of present study was to develop a high-throughput and selective HPLC method for evaluating the DPPH free radical scavenging activity of compounds and to evaluate the antioxidant capacity of eight drugs and nutrients commonly used in IBD treatment. Methods: Chromatographic analysis was performed using Agilent 1100 HPLC with diode array detector. XBridge C18 column (3.5 µm particle size, 4.6 × 150 mm) by Waters was used as stationary phase. Isocratic elution was applied using a 80:20 (v/v) mixture of methanol and ultrapure water. DPPH assay was monitored with diode array detector at 517 nm at 25°C with total run time of 5 min. Scavenging strength of compounds was shown using TROLOX as standard antioxidant and it was expressed as TROLOX equivalent antioxidant capacity (TEAC). It was calculated through the obtained calibration curve which presented linearity between 0.01 mM and 0.14 mM range ( R 2 = 0.99). Results: The highest antioxidative activity was found for 0.1 mM mesalazine (up to 310 times stronger than others) followed by aminosalicilates, sulfasalazine and balsalazide. On the other hand, olsalazine has shown no antioxidant activity. Furthermore, antioxidative nature of 1 mM solutions of immunosuppressant drugs was observed: 6-mercaptopurine and 6-thioguanine showed twice as much antioxidative power compared with azathioprine. Folic acid showed poor antioxidant activity. Obtained results imply that majority of the antioxidative power of IBD drugs originates from free 5-ASA present in the structure, whilst that of immunosuppressants might originate from the purine ring and mercapto group. Conclusions: The proposed method was found to be useful for high-throughput screening of antioxidant activity of currently used drugs and biologically active compounds as well as new drug candidates for IBD treatments. This work has been supported in part by the Croatian Science Foundation under the project number [UIP-2017-05-3949]. This work has been supported in part by the European Union from the European Social Fund.